Effectiveness of Positive Psychotherapy in Improving Sexual Anxiety, Satisfaction, and Depression in Female Infertile Patients - Saffarinia, Majid; Mortezaei karahrody, Zohreh; Alipour, Ahmad (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the effectiveness of positive psychotherapy on sexual anxiety, satisfaction, and depression in female infertile patients. Methods: The study was a clinical trial with a pretest-posttest and follow-up design which selected 52 infertile women with sexual dysfunction who visited the infertility ward of Imam Hussein Hospital in Tehran province from June to September 2021 using the purposive sampling method and then randomly assigned them to the experimental group (n=26) and the control group (n=26). The experimental group received positive psychotherapy skills in eight 90-minute sessions, and the control group was on the waiting list. Both groups responded to the standard Sexuality questionnaires by Snell, Fisher, and Walters (1993) in three stages. Data analysis was performed using multivariate repeated-measures analysis of variance (ANOVA). Result: The results indicated that the positive psychotherapy intervention decreased sexual anxiety (F=65.76, P=0.001), sexual depression (F=99.36, P=0.001), and improved sexual satisfaction (F=40.73, P=0.001) in the experimental group, and the impact was stable at the follow-up stage (P=0.05). Conclusion: Positive psychotherapy can be utilized individually and in groups to treat sexual and psychological disorders related to infertility according to its nature and function by emphasizing the need to use new and effective psychological therapies.